2021
DOI: 10.3390/toxins13080519
|View full text |Cite
|
Sign up to set email alerts
|

Bothrops Jararaca Snake Venom Modulates Key Cancer-Related Proteins in Breast Tumor Cell Lines

Abstract: Cancer is characterized by the development of abnormal cells that divide in an uncontrolled way and may spread into other tissues where they may infiltrate and destroy normal body tissue. Several previous reports have described biochemical anti-tumorigenic properties of crude snake venom or its components, including their capability of inhibiting cell proliferation and promoting cell death. However, to the best of our knowledge, there is no work describing cancer cell proteomic changes following treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 151 publications
(96 reference statements)
0
4
0
2
Order By: Relevance
“…GLUL, linked to tumor growth stimulation in BC, 42 was also identified as a responder in BC metabolism under hypoxic conditions in 2019 43 . GSTM3, within the GSTM4–GSTM2–GSTM1–GSTM5–GSTM3 cluster, has been associated with cancer susceptibility since 2010, 44 with subsequent studies affirming its role in BC 45–47 . GSK‐3 can modulate the sensitivity of MIA‐PaCa‐2 pancreatic and MCF‐7 BC cells to chemotherapy agents, targeted treatments and nutraceuticals, according to 2021 study, 48 and a connection between MIA and BC prevalence and progression was reported in 2014 49 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GLUL, linked to tumor growth stimulation in BC, 42 was also identified as a responder in BC metabolism under hypoxic conditions in 2019 43 . GSTM3, within the GSTM4–GSTM2–GSTM1–GSTM5–GSTM3 cluster, has been associated with cancer susceptibility since 2010, 44 with subsequent studies affirming its role in BC 45–47 . GSK‐3 can modulate the sensitivity of MIA‐PaCa‐2 pancreatic and MCF‐7 BC cells to chemotherapy agents, targeted treatments and nutraceuticals, according to 2021 study, 48 and a connection between MIA and BC prevalence and progression was reported in 2014 49 .…”
Section: Discussionmentioning
confidence: 98%
“…43 GSTM3, within the GSTM4-GSTM2-GSTM1-GSTM5-GSTM3 cluster, has been associated with cancer susceptibility since 2010, 44 with subsequent studies affirming its role in BC. [45][46][47] GSK-3 can modulate the sensitivity of MIA-PaCa-2 pancreatic and MCF-7 BC cells to chemotherapy agents, targeted treatments and nutraceuticals, according to 2021 study, 48 and a connection between MIA and BC prevalence and progression was reported in 2014. 49 ACTL8 has been consistently linked with poor BC prognosis in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Enfim, há também atividades envolvendo o uso do veneno de Bothrops jararaca como modulador de alvos protéicos ligados às células cancerígenas, em que o veneno em si ou alguns de seus componentes demonstraram a capacidade de inibir a proliferação de células cancerígenas, bem como ter o potencial de ser utilizado para a detecção de novos alvos para o tratamento de câncer (Kisaki et al, 2021). Em adição, foram relatados possíveis protótipos de antimicrobianos para o desenvolvimento de novos antibióticos contra bactérias resistentes aos atuais medicamentos (Ferreira et al, 2011).…”
Section: Potencial Terapêutico Do Gênero Bothrops Sp Com êNfase Em Bo...unclassified
“…Posto isso, é notável a ausência de patentes direcionadas ao desenvolvimento de agentes antimicrobianos, antivirais, antiparasitários e até mesmo anticancerígenos, uma vez que estudos já relataram esse potencial (Muller et al, 2012;Ferreira et al, 2011;Adade et al, 2014;Badari et al, 2021;Kisaki et al, 2021). O atual cenário revela uma ênfase no desenvolvimento de terapias para tratar alteração no sistema de coagulação, acrescido de uma tímida iniciativa para descobrir novos biomarcadores para a detecção de diversas doenças.…”
Section: Situação Legal E Distribuição Geográica Das Famílias De Pate...unclassified
“…We selected 19 original articles and 4 reviews approaching several points of Toxinology. The venom of snakes was approached in different aspects as the structural and functional variability in the composition of venoms from individual snakes [1], the mechanisms of action of whole venoms [2,3], the mechanisms of action of individual components as crotoxin [4], phospholipases A2 [5], metalloproteinases [6][7][8], and the oral immunity induced by whole venoms and their components [9]. Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16].…”
mentioning
confidence: 99%